Parameters estimation of photovoltaic models using a novel hybrid seagull optimization algorithm - Long, Wen; Jiao, Jianjun; Liang, Ximing; Xu, Ming; Tang, Mingzhu; Cai, Shaohong (Energy (Oxford), 2022)
Estimating parameters and establishing high-accuracy and high-reliability models of photovoltaic (PV) modules by using the actual current-voltage data is important to simulate, model, and optimize the PV systems. Several meta-heuristic optimization techniques have been developed to estimate the parameters of the solar PV models. However, it is still a challenging task to accurately, reliably, and quickly estimate the unknown parameters of PV models. This paper proposes a novel hybrid seagull optimization algorithm (HSOA) for estimating the unknown parameters of PV models effectively and accurately. In proposed HSOA, the personal historical best information is embedded into position search equation to improve the solution precision. A novel nonlinear escaping energy factor based on cosine function is presented for balancing global exploration and local exploitation. The differential mutation strategy is introduced to escape from the local optima. We firstly select twelve classical benchmark test functions to investigate the feasibility of HSOA, and experimental results show that HSOA is superior to most compared methods. Then, HSOA is used for solving parameters estimation problem of three benchmark solar PV models. The comparison results demonstrate that HSOA is superior to BOA, GWO, WOA, HHO, SOA, EEGWO, and ISCA on solution quality, convergence and reliability. •A hybrid algorithm called HSOA is proposed.•HSOA is applied to estimate the unknown parameters of PV models.•A modified position updating equation is presented.•A new nonlinear escaping energy strategy is designed.•Experimental results show the competitive performance of HSOA.